I am stuck on a question that involves the intergral of a periodic function. The question is phrased as follows:

Definition. A function is periodic with period $a$ if $f(x)=f(x+a)$ for all $x$.

Question. If $f$ is continuous and periodic with period $a$, then show that $$\int_{0}^{a}f(t)dt=\int_{b}^{b+a}f(t)dt$$ for all $b\in \mathbb{R}$.

I understand the equality, but I am having trouble showing that it is true for all $b$. I've tried writing it in different forms such as $F(a)=F(b+a)-F(b)$. This led me to the following, though I am not sure how this shows the equality is true for all $b$,

$$\int_{0}^{a}f(t)dt-\int_{b}^{b+a}f(t)dt=0$$ $$=F(a)-F(0)-F(b+a)-F(b)$$ $$=(F(b+a)-F(a))-F(b)$$ $$=\int_{a}^{b+a}f(t)dt-\int_{0}^{b+a}f(t)dt=0$$

So, this leaves me with


I feel I am close, and I've made myself a diagram of a sine function to visualize what each of the above integrals might describe, but the power to explain the above equality evades me.

  • 2
    $\begingroup$ See here for some proofs. $\endgroup$ – t.b. Jan 12 '12 at 8:09
  • $\begingroup$ (Voted to close as duplicate) Even though this says continuous and the other says integrable, the proofs are the same, i.e. every proof here would apply over there. $\endgroup$ – 6005 Jul 17 '16 at 16:25

Let $H(x)=\int_x^{x+a}f(t)\,dt$. Then $$\frac{dH}{dx}=f(x+a)-f(x)=0.$$ It follows that $H(x)$ is constant. In particular, $H(b)=H(0)$.


We have $$ \int_{0}^{a}f(t)\ dt+\int_{a}^{a+b}f(x)\ dx=\int_{0}^{b}f(y)\ dy+\int_{b}^{a+b}f(t)\ dt, $$ and setting $x=y-a$ turns the second integral into the third one.


No differentiation is needed:

Pick the unique integer $n$ such that $b\leqslant na\lt b+a$, decompose the integral of $f(t)$ over $t$ from $b$ to $b+a$ into the sum of the integrals from $b$ to $na$ and from $na$ to $b+a$, apply the changes of variable $t=x+(n-1)a$ in the former and $t=x+na$ in the latter, then the periodicity of $f$ implies that $f(x)=f(t)$, hence the result is the sum of the integrals of $f(x)$ over $x$ from $b-(n-1)a$ to $a$ and from $0$ to $b-(n-1)a$...

...Et voilà !


You have made various false steps in your four line block and should have ended up with $$\int_{a}^{b+a}f(t)dt-\int_{0}^{b}f(t)dt=0$$ but this does not take you much further forward.

Instead note that somewhere in the interval $[b, b+a]$ is an integer multiple of $a$, say $na$. Then using $f(t)=f(t+a)=f(t+na)$: $$\int_{b}^{b+a}f(t)dt = \int_{b}^{na}f(t)dt+\int_{na}^{b+a}f(t)dt = \int_{b+a}^{(n+1)a}f(t)dt+\int_{an}^{b+a}f(t)dt = \int_{na}^{(n+1)a}f(t)dt = \int_{0}^{a}f(t)dt.$$


$$\begin{align} \int_{b}^{a+b}f(x)\ dx&= \int_{a}^{a+b}f(x)\ dx +\int_{b}^{a}f(x)\ dx\\&\overset{y=x-a}{=} \color{red}{\int_{0}^{a}f(y+a)\ dx} +\int_{b}^{a}f(x)\ dx\\&\overset{periodic}{=} \color{red}{\int_{0}^{b}f(y)\ dx} +\int_{b}^{a}f(x)\ dx\\&=\int_0^af(x)\ dx. \end{align}$$

  • $\begingroup$ why a down vote here $\endgroup$ – Guy Fsone Jan 18 '18 at 8:15
  • $\begingroup$ The integral is obtained in the second line itself. You have done a calculation mistake. $\endgroup$ – Robin Feb 17 '18 at 8:56
  • $\begingroup$ Furthermore, this plagiarizes simultaneously three other answers, posted six years before. $\endgroup$ – Did Feb 18 '18 at 15:23

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.